Dakwah Kepada Orang Asli di Malaysia: Permasalahan dan Halangan - Syed Hussin, Syed Abdurahman (Jurnal Usuluddin, 2009)
This article discusses the problems and obstacles in the propogation of indigenous people in Malaysia. These problems and obstacles, if not addressed will slow efforts to intergrate them into a multiracial society, especially the Malay Muslim community. There are three main problems and obstacles that slow the missionary efforts of this group. Firstly, problems and obstacless related to Da`wah institutions and preachers themselves. Secondly, problems related to Muslim community in particular with the neighboring villages of indigenous peoples. Finally, problems related to da’wah own targets. All these problems and obstacles can be categorized into the internal problems and obstacles. Futhermore, there are also some problems and obstacles that could be categorized as an external problem such as the dissemination of Christianity, Bahai and Qadyani, the interference of Chinese traders and those who are irresponsible in taking opportunities on the degeneration of aboriginal community.